Forgotten hygiene: exploring menstrual self-care skills and parents awareness in adolescents with intellectual disability. - Elma, Ceren; Bilge, Çiğdem (International Journal of Developmental Disabilities, 2025)
Objectives: This study aimed to assess menstrual hygiene practices of adolescent girls with intellectual disability and their parents' related knowledge. Methods: A descriptive cross-sectional study was conducted with 30 adolescent girls enrolled in a special school. Data were collected using three instruments: Adolescent and Parent Information Form, Adolescent Menstrual Hygiene Behavior Assessment Form, and Adult Menstrual Hygiene Behavior Assessment Form. Results: Although some adolescents demonstrated basic hygiene skills such as changing underwear (46.7%) and washing hands (40.0%) independently, many needed assistance to recognize the onset of menstruation (53.3%) and to change sanitary pads regularly (23.3%). Only 26.7% were able to wipe the perineal area correctly. The parents' knowledge were also limited. Only 40.0% knew that they should wash their hands before going to the toilet and 46.7% knew the correct intervals for changing sanitary pads. The average knowledge score of parents were 6.47 ± 2.33 out of 12 points. Conclusions: There are still significant knowledge gaps in the area of menstrual hygiene among both adolescents with intellectual disability and their parents. Targeted, cognitively appropriate education programs are crucial for improving health, autonomy and social integration.